Acute metronidazole-induced neurotoxicity: an update on MRI findings. Issue 3 (March 2020) - Patel, L.; Batchala, P.; Almardawi, R.; Morales, R.; Raghavan, P.
Abstract : AIM: To describe a series of 10 cases of metronidazole-induced neurotoxicity (MIN) and review the established literature to better define its clinical and imaging findings. MATERIALS AND METHODS: The clinical presentations and magnetic resonance imaging (MRI) images of 10 patients with clinically diagnosed MIN were reviewed retrospectively. A review of an additional 31 cases from prior published case series was performed. RESULTS: The median age of patients from the authors' institutions with MIN was 54 (range 8–84) years. The median cumulative dose of metronidazole received was 64.5 g (range 7.5–1, 380 g). Common presenting neurological symptoms were ataxia ( n= 6) and altered mental status ( n= 3). All of the patients ( n= 10) had symmetric T2 hyperintense lesions in the dentate nuclei at presentation. Other involved structures included the midbrain, corpus callosum, pons, medulla, basal ganglia, and supratentorial white matter. True restricted diffusion was seen in the corpus callosum ( n= 6). Symptoms resolved in all patients except for one. For the patients with available follow up MRI ( n= 4), the observed lesions resolved. CONCLUSION: MIN affects both adult and paediatric patients. Symptoms typically occur after prolonged exposure to the antibiotic, but can occur at low cumulative doses. Most frequently involved structures are the dentate nucleus, midbrain, and splenium corpus callosum. Restricted diffusion within the corpus callosum is likely due to cytotoxic oedema. Symptoms typically resolve after cessation of metronidazole, and lesions typically resolve on follow-up imaging. Highlights: Metronidazole induced neurotoxicity affects patients of all ages and may not be dose dependent. Classic imaging findings include bilateral symmetric T2 hyperintense lesions in the dentate nuclei and midbrain. Lesions in the corpus callosum may exhibit restricted diffusion. Symptoms, and imaging findings, typically resolve after cessation of metronidazole.